(untitled) (Avocetta, 2023)
Italian Ornithological Commission (COI) - Report 31. This report refers to records from January 1st 2022 to December 31st 2022, with the addition of a number of records from previous years that were submitted more recently. For each species, the records are listed by date and information is given as follows: English and scientific name, number of accepted records pre- and post-1950 (the numbers in this abstract refer to the total number of records), number of individuals if more than one, age or plumage and sex if known, location, date, names of the observers, and available documentation (photograph, sound recording, specimen, etc.). According with the new CISO-COI Italian Checklist, which also includes subspecies, the taxonomy follows the HBW-BirdLife Check-list, as decided by the CISO council in 2018. A total of 40 records involving 31 taxa were assessed. The following 30 records, involving 22 taxa, were accepted, including six first records for Italy (Cat. AERC: A – COI Category 1A, 1B): Red-footed Booby Sula sula (Campania 2022; 1st record); White-tailed Lapwing Vanellus leucurus (Apulia 2022; 7th record); White-rumped Sandpiper Calidris fuscicollis (Latium 2022; 3rd record); Sharp-tailed Sandpiper Calidris acuminata (Sardinia 2022; 1st record); Franklin’s Gull Larus pipixcan (Liguria 2022; 6th record); Bonaparte’s Gull Larus philadelphia (Veneto 2022; 1st record); Glaucous Gull Larus hyperboreus (Veneto 2021; 20th record); Arctic Herring Gull (Vega Gull) Larus smithsonianus vegae (Marche 2022; 1st record); Roseate Tern Sterna dougallii (Friuli-Venezia-Giulia 2022; 5th record); Levant Sparrowhawk Accipiter brevipes (Latium 2021; 12th record ); East Siberian Merlin Falco columbarius insignis (Piedmont 1952; 1st record); Red-eyed Vireo Vireo olivaceus (Sicily 2022; 2nd record); Desert Shrike Lanius excubitor elegans/algeriensis (Campania 2021, Sicily 2022; 12th-13th record); Steppe Grey Shrike Lanius excubitor pallidirostris (Calabria 2022; 9th record); Brown Shrike Lanius cristatus (Tuscany 2021, Calabria 2021; 3rd-4th record); Isabelline Shrike Lanius isabellinus (Sicily 2021, Apulia 2022; 10th-11th record); Bar-tailed Lark Ammomanes cinctura (Sicily 2021, 2022; 5th-6th record); Olivaceus Warbler Iduna pallida (Sicily 2021; 14rd15th record); Eastern Bonelli’s Warbler Phylloscopus orientalis (Sicily 2010, 2022; Apulia 2022; 6th-8th record); Black-throated Wheatear Oenanthe seebohmi (Latium 2022; 2nd record); Caspian Stonechat Saxicola torquatus hemprichii (Latium 2022, Tuscany 2022; 6th-7th record); Eastern Yellow Wagtail Motacilla tschutschensis (Sicily 2021; 1st record). The addition of Red-footed Booby, Sharp-tailed Sandpiper, Bonaparte’s Gull, Arctic Herring Gull and Easter Yellow Wagtail Kittlitz’s Plover brings the Italian list to 562 accepted species. Records not accepted (COI List 5A, 5B) were: White-rumped Swift Apus caffer (Latium 2021); Pacific Golden Plover Pluvialis fulva (Emilia Romagna 2022, Apulia 2022); White-cheeked Tern Sterna repressa (Friuli-Venezia-Giulia 2022); Oriental Honey-buzzard Pernis ptilorhynchus (Calabria 2021); Arctic Warbler Phylloscopus borealis (Calabria 2022); Siberian Thrush Geokichla sibirica (Tuscany 2021); Oriental Reed-warbler Acrocephalus orientalis (Emilia Romagna 2022); Western Yellow Wagtail Motacilla flava flavissima (Tuscany 2005).